The role of fibroblast growth factor 21 in the pathogenesis of liver disease: a novel predictor and therapeutic target. (1st November 2014) - Liu, Wen-Yue; Huang, Sha; Shi, Ke-Qing; Zhao, Chen-Chen; Chen, Li-Li; Braddock, Martin; Chen, Yong-Ping; Feng, Wen-Ke; Zheng, Ming-Hua
Abstract : Introduction: Fibroblast growth factor 21 (FGF21) is one of the FGF family members that is produced mainly by tissues with high metabolic activity such as liver, pancreas, muscle and adipose tissue. The major function of FGF21 is to improve insulin sensitivity, ameliorate hepatic steatosis and enhance energy expenditure. Recently, several studies have reported a correlation between FGF21 and liver disease with numerous cross-sectional studies demonstrating significant correlation. This review will focus on the role of FGF21 in the pathogenesis of liver disease and its potential role as a biomarker and a new target for therapeutic intervention. Areas covered: This review discusses cross-sectional studies and underlying mechanisms of FGF21 as an endocrine hormone in several liver diseases. Two major theories of 'endoplasmic reticulum stress' and 'FGF21 resistance' in particular are explained. Moreover, early functional detection and pharmacological effect of FGF21 for liver disease are also described. Expert opinion: FGF21 can be a promising treatment in liver disease. However, still several problems are needed to be answered. The most important are whether different liver disease share common underlying mechanisms and the pharmacological effect in human with limited studies. Further studies are needed to explain the underlying mechanisms and develop potential therapeutic effect for human liver disease.